Electrocardiographic features of Wolff-Parkinson-White syndrome. Issue 5 (3rd September 2003) - Keating, L; Morris, F P; Brady, W J
Abstract : Wolff-Parkinson-White syndrome is not uncommon in the emergency department. Its early recognition and initial treatment allows rapid restoration to sinus rhythm. Prompt referral to cardiology is essential for risk stratification through electrophysiological studies.